Estrogen, aryl hydrocarbon and pregnane X receptors activities in reclaimed water and irrigated soils in Oued Souhil area (Nabeul, Tunisia) - Mahjoub, O.; Leclercq, M.; Bachelot, M.; Casellas, C.; Escande, A.; Balaguer, P.; Bahri, Akissa; Gómez, E.; Fenet, H. (Elsevier, 2009)
Secondary effluents (SE) contain xenobiotic organics (XO) that may cause disturbance in living organisms. When SE are reused in agriculture, contamination of soils by XO is of concern. In this study, SE used for irrigation/aquifer recharge in Oued Souhil area (Nabeul, Tunisia), as well as effluents irrigated soils, were tested for their XO load. Estrogen receptor (ER), aryl hydrocarbon receptor (AhR) and pregnane X receptor (PXR) in vitro based bioassays were used to assess potential activities of XO. Results were expressed as estrogen equivalent (E2 Eq), dioxin equivalent (TCDD Eq) and rifampicine equivalent (Rf Eq). Reclaimed water showed activities with 77.58 pM E2 Eq/L, 319.5 pM TCDD Eq/L and 197 nM Rf Eq/L. Instrumental analysis (GC/MS) revealed the presence of nonylphenol isomers mixture (NPm) (6600 ng/L) and pyrene (32 ng/L). In infiltration basin soil, activities and chemical compounds were the same as those detected in reclaimed water. In the irrigated plot, no estrogenic activity was observed, though AhR and PXR activities were detected. These results emphasize the transfer of active XO from reclaimed water to soils and their relative persistence. Further studies on mobility and persistence of mid-polar and polar active XO in soils should be examined in order to explain the observed activities.